The Role of Information Communication Technologies in Adult Education Theory Building - Judith Parker (Adult Education Research Conference, 2014)
The role of information communication technology in the development of the field of adult education will be explored. The changing image of the field will be presented and suggest how today’s Web 2.0 technology can enhance theory building and enrich the future of the profession.